Perceptions and Expectations of First-Year Medical Students at the Beginning of their Studies for their Course in the Field of Medicine - Evangelidis, Paschalis; Evangelidis, Nikolaos; Foti, Maria; Avramidou, Eleni; Kotave, Christina; Smyrnakis, Emmanouil (International Journal of Medical Students, 2025)
BACKGROUND: Studies conducted on first-year medical students around the world show that the common axis of their concerns is both finding the balance between workload and personal life, as well as the need to develop soft skills to interact with patients. This study explores the perceptions and expectations of first-year students at the School of Medicine of the Aristotle University of Thessaloniki regarding the course of their studies and their future careers at the beginning of their studies. METHODS: This is a cross- sectional study. The data was collected through an anonymous online questionnaire and completed by first-year students during their first lecture in October 2023. Descriptive statistical methods were used to analyze qualitative and quantitative variables. Braun and Clarke's method was used for the thematic analysis of the open questions by two independent researchers. RESULTS: The questionnaire was answered by 157 people out of the 233 people who participated in the (response rate: 67.4%). The 51.6% of the participants were men. The School of Medicine of the Aristotle University of Thessaloniki was the first choice for 126 (80.3%) students. The majority of students reported that they are quite confident in choosing medicine for their studies and career [median: 9, interquartile range (IQR) 2], while a significant percentage of students consider it likely to practice medicine abroad (median: 6, IQR: 3). Their expectations include enrichment of their knowledge, achievement of professional success, completion of their studies in a fair time. Some students prioritize social contribution as the major aim of their career. The main concerns included insecurity about their employment, lack of free time, possible wrong choice of studies, and fear of long-term commitment to medicine. In addition, 41 (26.1%) participants consider it likely to work in primary health care units after their studies. CONCLUSION: The majority of students feel confident in choosing medicine as a profession. Resolution of their fears and concerns through close communication between students and teaching staff is considered necessary.